2024
DOI: 10.7189/jogh.14.05008
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and emergence of new neuropsychological deficits following SARS-CoV-2 infection: A follow-up assessment of the Geneva COVID-COG cohort

Philippe Voruz,
Isabele Jacot de Alcântara,
Anthony Nuber-Champier
et al.

Abstract: Background Despite numerous observations of neuropsychological deficits immediately following severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, little is known about what happens to these deficits over time and whether they are affected by changes in fatigue and any psychiatric symptoms. We aimed to assess the prevalence of neuropsychological deficits at 6–9 months and again at 12–15 months after coronavirus disease 2019 (COVID-19) and to explore whether it was associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…No associations were detected between longitudinal changes in cognitive and mental health measures. Conversely, a previously published work found that changes in executive functions were significantly associated with changes in depressive symptoms 57 .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…No associations were detected between longitudinal changes in cognitive and mental health measures. Conversely, a previously published work found that changes in executive functions were significantly associated with changes in depressive symptoms 57 .…”
Section: Discussionmentioning
confidence: 88%
“…Our results are in line with previous published works showing both improvements and persisting cognitive deficits in PACS 55 , 56 . Previous research has also documented a decline in executive functions among participants who initially presented with severe cognitive impairment 57 . The repeated administration of a cognitive test four times over a six-month period in our study raises concerns about the potential influence of a learning effect on the results.…”
Section: Discussionmentioning
confidence: 93%